Addressing teachers' concerns about the Prog&Play serious game with context adaptation. (1st January 2012) - Muratet, Mathieu; Delozanne, Elisabeth; Torguet, Patrice; Viallet, Fabienne
Video games are supposed to provide a good learning environment. We study a large-scale use (260 students and 20 teachers) of Prog&Play, a serious game specially designed to teach computer programming fundamentals. In earlier quantitative studies, we found, through a students' motivation survey, that the students' interest for Prog&Play was not only related to the intrinsic game quality, it was also related to the teaching context. In this paper, we investigate contextual effects that influence motivational and learning benefits while using Prog&Play in different teaching settings. Results from a qualitative study of 41 students' and 18 teachers' comments, suggest guidelines for a successful implementation of Prog&Play.